'A Petty Form of Suffering': A Brief Cultural Study of Itching. (June 2018) - Segal, Naomi
'Itching is a petty form of suffering, ' wrote André Gide in 1931. Itching may be occasional or obsessive; it positions a person inside a body that exists in familial and social contexts; it can be evoked in debates about righteousness and justice. This article begins with discussion of the work of Didier Anzieu, psychoanalyst author of The Skin-ego : among the nine 'functions' of the skin-ego that Anzieu describes, the last is 'toxicity', the skin turned against itself in a gesture of self-destruction. In my discussion of three other texts, I connect Gide's diary entry to his sexuality; Lorette Nobécourt's novel to the social world; the book of Job to the metaphysics of virtue; and to these I append two semi-comic moments from Jean-Paul Sartre and Sarah Winman, and discussions of 'leprosy' and psoriasis, two versions of feeling (in both senses) that one has a skin.